2014
DOI: 10.1080/08927022.2014.907899
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in molecular simulation approaches to study spherical virus capsids

Abstract: Viruses are a particularly challenging systems to study via molecular simulation methods. Virus capsids typically consist of over 100 subunit proteins and reach dimensions of over 100 nm; solvated viruses capsid systems can be over 1 million atoms in size. In this review, I will present recent developments which have attempted to overcome the significant computational expense to perform simulations which can inform experimental studies, make useful predictions about biological phenomena and calculate material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 104 publications
0
23
0
Order By: Relevance
“…Providing information about molecular properties of drugs (ADME/T, PK/PD model, chemical space analysis and drug-likeness evaluation) [1][2][3][4][32][33][34][35][36] Identification of drug-target interaction Predicting and evaluating drug/compound-target interaction (molecular docking, molecular dynamics simulation, machine learning and similarity analysis) [37][38][39][40][41][42] Network level Drug-target network analysis…”
Section: Molecular Level Evaluation Of Molecular Characteristicsmentioning
confidence: 99%
“…Providing information about molecular properties of drugs (ADME/T, PK/PD model, chemical space analysis and drug-likeness evaluation) [1][2][3][4][32][33][34][35][36] Identification of drug-target interaction Predicting and evaluating drug/compound-target interaction (molecular docking, molecular dynamics simulation, machine learning and similarity analysis) [37][38][39][40][41][42] Network level Drug-target network analysis…”
Section: Molecular Level Evaluation Of Molecular Characteristicsmentioning
confidence: 99%
“…Often, capsids play key functional roles in delivering the viral genome to the host cell nucleus, rendering them of great interest as drug targets. Capsids generally represent the largest protein components of virus structures, and simulations of intact capsids have accounted for the most substantial all-atom virus simulations yet published [106, 2]. Work by Perilla et al has clearly demonstrated the need for chemical detail to facilitate accurate simulation studies of virus capsids as drug targets [107].…”
Section: Capsidsmentioning
confidence: 99%
“…Prior to work on STMV, simulations of complete capsids were approximated using rotational symmetry boundary conditions, which exploit the icosahedral symmetry of capsid structures to model, at least in effect, a complete capsid using only the capsid asymmetric unit [106]. As time has progressed, all-atom simulations of intact capsids have become increasingly accessible.…”
Section: Capsidsmentioning
confidence: 99%
“…First, for any non-negative integer n (say, n=5), the radial displacement w can be determined by Eq. (26), and the three dimensionless natural frequencies can be obtained through Eq. (13) (see Fig.…”
Section: B Non-axisymmetric Free Vibration Of a Biopolymer Sphericalmentioning
confidence: 99%
“…Yang et al 22 predicted vibrational modes of several icosahedral viruses and an icosahedral enzyme using continuum models, and they estimated the macroscopic material properties such as the Young's modulus or Poisson's ratio by fitting the predictions to an anisotropic network model. May and Brooks [23][24][25][26] applied two-dimensional elasticity theory to viral capsids and developed a framework for calculating elastic properties of viruses.…”
Section: Introductionmentioning
confidence: 99%